Evolution of principal stress of a turbine rotor under cyclic thermo-mechanical loading. (January 2020) - Liu, Yang; Wang, Weizhe
Highlights: Creep-fatigue interaction is fully considered in the rotor behavior analysis. Different effects of principal and Mises stresses on the rotor design are discussed. Three potential failure locations are chosen for the study of principal stress. Principal stress evolution under cyclic thermo-mechanical loading is described. Abstract: The target of the present study is to analyze the local variation of stress and strain state in a steam turbine rotor under cyclic service-type thermo-mechanical creep-fatigue loading conditions. Toward this end, a Chaboche model based material constitutive model is applied to simulate the multi-axial stress-strain behavior in the rotor. Comparison of von Mises stress, stress tensors and principal stresses is carried out to demonstrate the importance of the stress state which is very useful to the optimization of the components and operation, and then principal stress and strain during a whole cyclic loading condition is analyzed to illustrate the variation of tension and compression states. Both the temperature and rotating speed related centrifugal force influence the evolution of the principal stresses and strain, but the influential extent has a large difference at different locations; furthermore, the discrepancy of cyclic softening/hardening behavior and ratcheting behavior due to creep at different locations is also significant. This outcome can be used to carry out the optimization or damage assessment in the rotor.